Parent–Adolescent Communication and Problematic Internet Use: The Mediating Role of Fear of Missing Out (FoMO). (September 2018) - Alt, Dorit; Boniel-Nissim, Meyran
With the growing attention paid to the role of Fear of Missing Out (FoMO) as a mediator, linking deficits in psychological needs to Problematic Internet Use (PIU), this study explored the role of FoMO in partially explaining the connection between parent–child communication and the child's PIU. Data were gathered from 270 participants of whom 45.6% 13- to 15-year-old youth (middle school students), and 54.5% 15.5- to 18-year-old adolescents (high school students). Path analysis results have corroborated the main research hypothesis, according to which positive communication activities of parents, such as listening to their children, trying to understand how they feel and what they think, and creating a positive and supportive atmosphere for discussions, can reduce FoMO experiences among adolescents, which in turn might decrease their PIU. Limitations, conclusions, and directions for further research are discussed.